2015
DOI: 10.1039/c5ra00224a
|View full text |Cite
|
Sign up to set email alerts
|

A highly-deformable piezoresistive film composed of a network of carbon blacks and highly oriented lamellae of high-density polyethylene

Abstract: The electrical resistance change of highly extensible films consisting of a network of carbon blacks in highdensity polyethylene, with different regularity of stacked lamellae, is investigated. The film was fabricated by melt mixing of high-density polyethylene (HDPE) and carbon black (CB) via cast film extrusion. The morphology of particle network and regularity of stacked lamellae were affected by draw ratio during the cast film extrusion process. Testing has shown that the regularly stacked lamellar structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…This can be supported by the distribution and arrangement of CNTs and CB in the PVDF matrix as observed for 0.5CNTs-0.5CB (referring to Figure a). This kind of network can be easily deformed and broken under tensile loading due to movement/slippage of CB particles and thus is more susceptible to strain. However, for the nanocomposites containing CNT contents above Φ CNTs , much denser structures are observed.…”
Section: Results and Discussionmentioning
confidence: 99%
“…This can be supported by the distribution and arrangement of CNTs and CB in the PVDF matrix as observed for 0.5CNTs-0.5CB (referring to Figure a). This kind of network can be easily deformed and broken under tensile loading due to movement/slippage of CB particles and thus is more susceptible to strain. However, for the nanocomposites containing CNT contents above Φ CNTs , much denser structures are observed.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Several authors investigated the evolution of the electrical behaviour of CB/polymer composites under cyclic loading [14][15][16][17] and viscoelastic relaxation phenomena but just few of them have pointed out "Mullins-like" hysteresis effects [15,17]. Among the few studies dealing with the phenomenon of electrical hysteresis in nanocomposite materials, De Focatiis et al [15] reported that the resistivity-strain relationship for rubber materials exhibits a dependence on the history of the mechanical deformation.…”
Section: Introductionmentioning
confidence: 99%
“…This is essentially achieved through a rational sensor design process, that is, properly selecting the hybrid material systems and processing through a fabrication recipe commensurate with a desired application. Most recently developed fabrication processes use carbon‐based nanomaterials including carbon nanotubes, carbon black, and graphene to assemble the deformable conductive network owing to their availability and superior electrical properties. It is desirable to lower the concentration of conductive filler to augment the sensor sensitivity while retaining stretchability of the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%